2009
DOI: 10.1590/s0104-42302009000400018
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia do contorno corporal no paciente após perda ponderal maciça: experiência de três anos em hospital público secundário

Abstract: submetidos a tratamento de obesidade mórbida por meio de gastroplastia redutora, com sucesso para a técnica, ou emagrecimento por método não-cirúrgico. Os critérios de exclusão foram tabagismo, intenção gestacional e instabilidade ponderal, exigindo-se peso estável por pelo menos seis meses após atingido a perda ponderal satisfatória. resultados. Dos 98 pacientes operados, 97% eram do sexo feminino, com idade média de 40,5 anos e o método de emagrecimento foi cirúrgico em 88% deles. Das 177 cirurgias plásticas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
(56 reference statements)
3
4
0
11
Order By: Relevance
“…The mean score obtained on the Moorehead-Ardelt quality of life questionnaire applied to 36 patients was 2.18. The present study showed that the majority of the patients consisted of women, as well as other studies [13][14][15][16][17][18] . Likewise, the mean age of 41 years was similar to that of other works [15][16][17]19 , but below the age of 44 years in an American work 14 and 48 years evidenced by other series 13,20 .…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…The mean score obtained on the Moorehead-Ardelt quality of life questionnaire applied to 36 patients was 2.18. The present study showed that the majority of the patients consisted of women, as well as other studies [13][14][15][16][17][18] . Likewise, the mean age of 41 years was similar to that of other works [15][16][17]19 , but below the age of 44 years in an American work 14 and 48 years evidenced by other series 13,20 .…”
Section: Introductionsupporting
confidence: 88%
“…The present study showed that the majority of the patients consisted of women, as well as other studies [13][14][15][16][17][18] . Likewise, the mean age of 41 years was similar to that of other works [15][16][17]19 , but below the age of 44 years in an American work 14 and 48 years evidenced by other series 13,20 . The mean BMI before plastic surgery of 27.4kg/m 2 was similar to that found by other authors [13][14][15][16][17] , but well below the BMI of 35.6Kg/m 2 verified by Shermak et al 21 .…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Volterra et al 41 described the effects of neuroendocrine obesity induction on systemic hemodynamics and left ventricular function in normotensive rats. Orpheu et al 42 detected a time dependent increase in the demand for body contour surgery in massive weight loss patients from pretreatment through bariatric surgery and subsequently over a three-year follow up. Kurebayashi et al 43 analyzed nurses' perceptions about diseases that are treated by acupuncture and found that it was used to treat obesity among other morbid situations.…”
Section: Methodsmentioning
confidence: 99%